ACCEPTANCE OF THE COVID-19 VACCINE BASED ON THE HEALTH BELIEF MODEL IN SUMATRA BARAT PROVINCE - Haq, Arinil; Triana, Vivi; Oktari, Siska (HEARTY, 2026)
West Sumatra is in the bottom two ranks with the lowest percentage of willingness to accept the COVID-19 vaccine in Indonesia. This study aims to determine the factors associated with the acceptance of the COVID-19 vaccine based on the health belief model (HBM) in the community in West Sumatra Province in 2021. This study is an analytical observational study with cross-sectional study design. An online questionnaire was distributed to obtain participants ≥18 years old in West Sumatra Province who had never received the COVID-19 vaccine. A total of 266 participants completed the questionnaire form. The acceptance of COVID-19 vaccine was moderate (56,4%). The results of the bivariate analysis showed that there were significant relationship between perceived of benefits (p-value = 0.001), perceived of barriers (p-value = 0.029) and cues to action (p-value = 0.001) with COVID-19 vaccine acceptance. There were no significant relationship between perceived of susceptibility and perceived of severity with COVID-19 vaccine acceptance. It is important to provide accurate information about the disease, vaccines, and their benefits, as well as encourage government and healthcare professionals to increase vaccine acceptance.